2020
DOI: 10.1155/2020/7146701
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Expression Analysis of Sugar Transporter Gene Family in Aspergillus oryzae

Abstract: Sugar transporter (SUT) genes are associated with multiple physiological and biochemical processes in filamentous fungi, such as the response to various stresses. However, limited systematic analysis and functional information of SUT gene family have been available on Aspergillus oryzae (A. oryzae). To investigate the potential roles of SUTs in A. oryzae, we performed an integrative analysis of the SUT gene family in this study. Based on the conserved protein domain search, 127 putative SUT genes were identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 47 publications
2
6
0
Order By: Relevance
“…It was found that most of VdST proteins possessed 10-12 TMDs, and 8 proteins harbored only 7-9 TMDs, likely due to sequence deletion during gene evolution. Consistent with this, similar ST protein structures have been observed in many plants and other fungi ( Afoufa-Bastien et al., 2010 ; Reuscher et al., 2014 ; Lv et al., 2020 ). A phylogenetic analysis found that the 65 VdST genes were grouped into 8 Clades with specificity to different groups of sugar molecules, which was similar to research in other fungi ( Peng et al., 2018 ; Lv et al., 2020 ).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…It was found that most of VdST proteins possessed 10-12 TMDs, and 8 proteins harbored only 7-9 TMDs, likely due to sequence deletion during gene evolution. Consistent with this, similar ST protein structures have been observed in many plants and other fungi ( Afoufa-Bastien et al., 2010 ; Reuscher et al., 2014 ; Lv et al., 2020 ). A phylogenetic analysis found that the 65 VdST genes were grouped into 8 Clades with specificity to different groups of sugar molecules, which was similar to research in other fungi ( Peng et al., 2018 ; Lv et al., 2020 ).…”
Section: Discussionsupporting
confidence: 85%
“…Consistent with this, similar ST protein structures have been observed in many plants and other fungi ( Afoufa-Bastien et al., 2010 ; Reuscher et al., 2014 ; Lv et al., 2020 ). A phylogenetic analysis found that the 65 VdST genes were grouped into 8 Clades with specificity to different groups of sugar molecules, which was similar to research in other fungi ( Peng et al., 2018 ; Lv et al., 2020 ). Compared with Clade I, VI and VII, Clade IV, II, V, VIII and III harbored more members, mainly including hexose transporters, disaccharide (lactose and maltose) permeases, myoinositol transporters and quinate permeases.…”
Section: Discussionsupporting
confidence: 85%
“…We nally found 173 STs in A. sydowii H-1 genome. Compared with 127 and 86 STs in Aspergillus oryzae [71] and Aspergillus niger [72], this number is undoubtedly larger and indicate a high potential for substrate utilization. Through analysis, we obtained a phylogenetic tree similar to the sugar transporters in A. niger [72], which were divided into 9 subgroups including hexose, glucose, xylose, galactose, glycerol, inositol, sucrose and other transporter types (Fig.…”
Section: Conclusion and Discussionmentioning
confidence: 94%
“…In some Aspergillus species, the genes encoding proteins involved in sugar transport were already identified. For instance, A. oryzae and A. niger contain 127 [87] and 86 [88] putative sugar transporter genes, respectively. However, only a small number of these transporters has been functionally characterized [86] , [89] , [90] , [91] , [92] , [93] , [94] .…”
Section: Endocytosis Of Sugar Transportersmentioning
confidence: 99%